Inhibition of Peptidyl Arginine Deiminase 4-Dependent Neutrophil Extracellular Trap Formation Reduces Angiotensin II-Induced Abdominal Aortic Aneurysm Rupture in Mice - Wei, Ming; Wang, Xia; Song, Yanting; Zhu, Di; Qi, Dan; Jiao, Shiyu; Xie, Guomin; Liu, Ye; Yu, Baoqi; Du, Jie; Wang, Yuji; Qu, Aijuan (Frontiers in Cardiovascular Medicine, 2021)
Objective: Neutrophil infiltration plays an important role in the initiation and development of abdominal aortic aneurysm (AAA). Recent studies suggested that neutrophils could release neutrophil extracellular traps (NETs), leading to tissue injury in cardiovascular diseases. However, the role of NETs in AAA is elusive. This study aimed to investigate the role and underlying mechanism of NETs in AAA development. Methods and Results: Angiotensin II (Ang II) infusion-induced AAA model was established to investigate the role of NETs during AAA development. Immunofluorescence staining showed that citrullinated histones 3 (citH3), myeloperoxidase (MPO) and neutrophil elastase (NE) (NETs markers) expression were significantly increased in Ang II-infused ApoE-/- mice. Circulating double-stranded DNA (dsDNA) level was also elevated, indicating that increased NETs formation during AAA. PAD4 inhibitor YW3-56 inhibited Ang II-induced NETs formation. Disruption NETs formation by YW3-56 markedly reduced Ang II-induced AAA rupture, as revealed by decreased aortic diameter, vascular smooth muscle cells (VSMCs) apoptosis and elastin degradation. Apoptosis of VSMC was evaluated by TUNEL staining and Annexin V-FITC/PI staining through flow cytometry. Western blot and inhibition experiments revealed that NETs induced VSMC apoptosis via p38/JNK pathway, indicating that PAD4-dependent NETs formation played an important role in AAA. Conclusions: This study suggests that PAD4-dependent NETs formation is critical for AAA rupture, which provides a novel potential therapeutic strategy for AAA disease.